Platelet-rich plasma combined with intralesional triamcinolone acetonide for the treatment of alopecia areata: A case report - Thamer Mubki (Wolters Kluwer Medknow Publications, 2016)
Treatment of long standing alopecia areata can be extremely difficult. Combining more than one treatment modality may be needed. Promising results have been previously reported using platelet-rich plasma. However, combining this treatment modality with other therapies has never been evaluated. We report a patient with long standing alopecia areata treated with a combination of triamcinolone acetonide and platelet-rich plasma intradermal injections. The trial was performed in a half-head design. One half of the scalp was treated with both platelet-rich plasma and intralesional triamcinolone acetonide. The other half received intralesional triamcinolone acetonide only. The half head treated with the combined therapy showed more regrowing hairs and larger hair fiber diameter. Our limited findings suggest that combining platelet-rich plasma with intradermal triamcinolone acetonide may have a positive synergistic effect for treating alopecia areata. Controlled studies with a large number of patients are needed.